Readiness and Acceptance of Farmer Cards to Farmers in Sumenep Regency - Laras Nur fitriani; Darsono; Barokah, Umi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The Farmer’s Card becomes one of the requirements to get the subsidized fertilizer as a tool of access to banking services integrated into an E-wallet or ATM (Automatic Teller Machine). The new technology indicates the problem found in the field, which is the lack of awareness and knowledge of the farmers who own the Farmer’s Card in understanding the function of each feature provided by the Card. This research is conducted to analyze the readiness and the acceptance factors of the farmers who own the Farmer’s Card toward the interest of using the Farmer’s Card in the Sumenep Regency. The Technology Readiness and Acceptance Model (TRAM), which is the collaboration of the Technology Readiness Index (TRI) and Technology Acceptance Model (TAM), is being used to analyze the interest in the use of the Farmer’s Card. Quantitative data is collected through interviews with structured questionnaires that refer to the previous research indicators on the Technology Readiness and Acceptance Model (TRAM). The sample was conducted on 140 farmers who own the Farmer’s Card. The analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) through the SmartPLS software. The results of the hypothesis show that the function or the advantage of the Farmer’s Card has a direct and significant influence on the interest of the farmers in using the Farmer’s Card. On the other hand, the simplicity of using the Farmer’s Card is considered insignificant and challenging for the farmers. The Farmer’s Card program can be successful. It is suggested that the government and the farmers, who own the Farmer’s Card, need to approach and improve their communication through intensive guidance. Keywords: readiness, acceptance, farmer's card, PLS-SEM, subsidized fertilizer